Effect of Post Emergent Herbicides on Centaurea diluta Aiton Infecting Wheat in Ouazzane Region - Morocco - , B. Hajjaj; , A. El Oualkadi; , H. Tantaoui; , M. Chentouf (Archives of Current Research International, 2019)
High infestations of Centaurea diluta (Lesser star-thistle) become a serious problem to cereal farmers in Ouazzane region of Morocco. The aim of this study is to investigate the effect of three post-emergent herbicides on C. diluta infestation in a soft wheat crop. The experimental design was Randomized Complete Block Design (RCBD) with three replications. Each block contained 4 elementary plots, 3 plots of which were treated with the three post emergent herbicides and the untreated plots serving as control. Trials were conducted in Ouazzane region of Morocco in January 2017. Treatments were carried out with a knapsack sprayer with the nozzle delivering a 3 bar jet. Calculation of reduction of biomass in C. diluta was carried out at weed research laboratory of INRA-CRRA Tangier in March 2017 using an oven at 75ºC for 48 hours. The weights were then taken using a precision balance. A quadrant of 1 m2 was used to calculate the reduction of density in C. diluta. Results showed that treatment with Aminopyralid + Florasulam at (9.9 + 4.95) g/ha and 2,4-D at 600 g/ha gave the best control of C. diluta infestations. In fact, Aminopyralid + Florasulam at (9.9+4.95) g/ha recorded 88±4.1%, 86±5.1% and 97±1.6% respectively on reduction of density, height and biomass in C. diluta. 2,4-D at 600 g/ha recorded 75±3.1%, 84±4.2% and 94±2.5% respectively on reduction of density, height and biomass in C. diluta. Tribenuron-methyl at 9.50 g/ha recorded the lowest efficacies recording 25±4.9%, 21±4.8% and 37±8.1% respectively on reduction of density, height and biomass in C. diluta. Thus, Aminopyralid + Florasulam at (9.9+4.95) g/ha and 2,4-D at 600 g/ha could be recommended to farmers in Ouazzane region when C. diluta infestation is dominant on wheat. A further assessment of Aminipyralid and Florasulam residues in soil and their phytotoxicities should be evaluated on other crops grown in rotations.